pengembangan media pembelajaran pendekteksi detak jantung dan tensi meter digital portable berbasis arduino di prodi pendidikan teknik elektro - balsilio rae, alfiano; Adiarta, Agus; Ratnaya, I Gede (Jurnal Pendidikan Teknik Elektro Undiksha, 2023)
This study aims to create a learning media in the form of Arduino Uno-Based Digital Heart Rate Detection and Tension Meter learning tools in the Cooling Machine Installation Design course in the Bachelor of Electrical Engineering Education study program Undiksha. This research is included in the type of research (Analog to Digital Convert and Motor Driver). This study uses percentage statistical analysis techniques to process data from content experts, media experts, and trials on students. This study used a questionnaire as an instrument for data collection for content experts, media experts, and students. The results of the study obtained the results of the content expert validation test of 95.3% with very decent qualifications, the media expert validation test of 100% with very decent qualifications, small group trials of 5 respondents getting very decent qualification results, and large group trials of 10 respondents getting results with very high classification. Learning media in the form of Arduino Uno-Based Digital Heartbeat Detection and Tension Meter learning tools in Microcontroller courses in the Undiksha Electrical Engineering Education Study Program are suitable for use in the learning process of Microcontroller Design courses in the Undiksha Electrical Engineering Education Study Program.